DISPOSITION KINETICS OF DICLOFENAC IN FEMALE GOATS - Singh, Thakur Balwant; Singh, SD; Kumar, Nitesh; Sharma, CS (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The pharmacokinetic of diclofenac was studied in five clinically healthy female goats (Capra hircus) following i.v. administration (2 mg. kg-1 body weight). Blood and urine samples were collected at different time intervals and were analysed using HPLC. The plasma concentration–time data following i.v. administration of diclofenac was best described by a two compartment open pharmacokinetic model. Elimination half life (t1/2β), area under plasma concentration time curve (AUC), mean residential time (MRT), micro-rate constant of drug transfer from central to peripheral (K12) and peripheral to central compartment (K21) were noted as 2.97 ± 0.53 h, 19.40 ± 2.98 mg.L 1h, 2.62 ± 0.61 h, 1.710 ± 0.141 h-1and 0.514 ± 0.041 h-1 , respectively. Volume of distribution (Vdarea) and total body clearance (ClB) were 0.49 ± 0.11 L.kg-1 and 1.91 ± 0.33 ml.kg-1.min-1, respectively. Rate constant drug elimination from central compartment (Kel), fraction of drug available for elimination from central compartment (Fc) and approximate tissue to plasma concentration ratio (T H” P) were noted as 2.509 ± 0.884 h-1, 0.13 ± 0.02 and 8.16 ± 2.21, respectively. Low Vdarea, K21 and ClB with high K12, MRT supports high protein binding and localisation of diclofenac.
Keywords: Pharmacokinetics; Diclofenac; HPLC; I.V.; Goat